Effects of internal Acoustic Excitation on the Improvement of Airfoil Performance - Fayed, Ikhlase M. (Al-Khwarizmi Engineering Journal, 2007)
The effect of internal acoustic excitation on the leading-edge, separated boundary layers and the aerodynamic performance of NACA23015 cross section airfoil are examined as a function of excitation location with ranging frequency range (50-400) Hz of the introduced acoustic. Tests are separately conducted in two sections, open type wind tunnels at the Reynolds number of 3.3x105 for measurement at angle of attack (0, 3, 6, 9 &12) deg. and 3x104 for the visualization at angle of attack (12) deg. based on the airfoil chord. Results indicated that the excitation frequency and the excitation location are the key parameters to alter the flow properties and thus to improve the aerodynamic performance. The most effective excitation frequency is found to be equal to the shear layer instability frequency and on excitation location close to the separation point. Moreover, the lift is increased and drag reduced dramatically. The corresponding boundary layers are visualized to be reattached to the surface.